Rektorers rörlighet i Sverige: en kunskapsöversikt - Katina Thelin; Sandra Lund (Dalarna university, 2023)
What do we know about principal turnover in Sweden? The purpose of this article is to map and describe the current state of knowledge related to principal turnover in Sweden. The review covers literature published by researchers and Swedish authorities during the past decade, and is structured thematically to answer three questions: 1) What is the level of principal turnover in Sweden? 2) What are the causes of principal turnover in Sweden? 3) What are the consequences, and strategies used for dealing with principal turnover in Sweden? Based on the results it is concluded that the state of knowledge relevant to this area of concern is remarkably weak.